PENGARUH INVESTMENT OPPORTUNITY SET , LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP EARNING QUALITY (Media Riset Akuntansi, 2022)
This study aims to analyze how much investment opportunity set, liquidity,and firm size affect profit quality that listed on the Indonesia Stock Exchange period 2014- 2016. The population used in this study are all manufacturing companies thal listed in Indonesia Stock Exchange since 2014 to 2016 respectively. The sample selsction using purposive sampling method, with the acquisition of 123 samples in accordance with the criteria. Methods of data analysis used in this research is quantitative approach using multiple linear regression. Secondary data were obtained from the annual financial statement of listed manufacturing companies in the Indonesia Stock Exchange. Based on the research that has been done at the manufacturing companies listed on the Indonesia Stock Exchange, it can be inferred that investment opporutnity set influence profit quality. Meanwhile, liquidity and firm size it does not affect profit quality. These result assume liquidity and firm size have no affect to profit quality